Flaking stone activity in the tradition of iron smelting from the 8th to 17th centuries AD in the Matano region, South Sulawesi, Indonesia. (April 2021) - Suryatman,; Triwurjani, RR; Adhityatama, Shinatria; Bulbeck, David; Yurnaldi, Dida; Murdihastomo, Ashar; Wahyudiono, Joko; Abdullah,; Dimas Khoiru Dhony, Muslim
Highlights: Information on new iron smelting sites in the Matano Region, including those submerged underwater. Ethnographic data on the process of using chert artifacts as strike-a-lights by Matano villagers. Thousands of chert artifacts in contexts dating to the 8th to 17th centuries AD at the Rahampu'u site. Production of the cores and flakes used as the first-stage strike-a-lights. Reduction of the strike-a-lights during use accompanied by distinctive retouch. Abstract: Lake Matano includes a complex of sites related to an iron-smelting industry that developed at the northeast tip of South Sulawesi between the 8th and 17th centuries AD. The sites include recently discovered underwater sites which possibly submerged because of an earthquake that had occurred in the region. An interesting finding at each site is the presence of flaked artifacts from chert. This raises the question of what was the role of flaked chert in the local tradition of iron smelting. The present study was conducted by combining ethnographic data from Lake Matano and analysis of chert artifacts excavated from the Rahumpu'u lakeshore site. The results show that chert artifacts were used as strike-a-lights and in particular for the combustion of fuel for iron smelting. Flaking chert was one of the skills possessed by the Matano indigenous iron smelters in utilizing the resources in their environment to produce a high quality of iron.